The erosion of tradition in an age of globalization: Cultural hybridity and marginality in contemporary Yorùbá films - Akinsola, Ifeoluwa; Osundiran, Ebunoluwa Esther (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
Yorùbá films have developed over time owing to westernisation and technological advancements. Due to this development, contemporary Yorùbá films are easily accessible through the internet and social media. However, the cultural contents of these films remain questionable due to influences from the western world. Studies have identified the portrayal of Yorùbá culture, history and folklores in Yorùbá films with less emphasis on the way contemporary Yorùbá films have hybridised various cultures and possibly marginalised the Yorùbá culture as a result of westernisation and civilisation. The qualitative research approach, using document analysis was therefore adopted to examine cultural hybridity and marginality in contemporary Yoruba films. Four purposively selected films (Jagunjagun, Anikulapo, Agesinkole, and Elesin-Oba) constituted the texts analysed thematically and interpreted using the theories of Cultural Hybridity and Cultural Marginality. Findings revealed that the selected films portray the hybridisation of Yorùbá culture with other cultures, while marginalising the Yorùbá culture in many cases. The paper argued that the film-makers’ quest for global acceptance and profit making are responsible for these hybridisation and marginalisation. Therefore, economy is at the centre of movie-making in Nigeria, irrespective of the cultural interest of both the film-makers and the audience.